The Political Economy of Indonesia’s Mining Downstreaming Policy: An Adam Smithian Analysis of the Joko Widodo Administration - Yogar, Bagaskoro Nur Abu; Ramdani, Rijal; Pranaja, Kevin Arya; Mutiara, Destita; Rifandi, Muhammad (JURNAL TRIAS POLITIKA, 2026)
Indonesia’s downstream mining policy under President Joko Widodo has emerged as a pivotal strategy to transform the national economy from resource extraction to industrial value creation. This study examines the policy’s effectiveness and socio-economic implications of the downstream mining policy using a qualitative descriptive approach supported by document analysis and secondary data from government reports, academic studies, and industrial statistics. The analysis is framed through Adam Smith’s classical economic theory, focusing on the principles of limited government intervention, division of labour, and public welfare. The findings reveal that the down streaming policy has successfully increased the export value of processed minerals, attracted investment in smelting industries, and generated employment opportunities. However, the benefits remain uneven due to regulatory inconsistency, rent-seeking practices, and environmental degradation in mining regions. From a theoretical standpoint, Indonesia’s case reflects both adherence to and divergence from Smithian ideals—combining state-led industrialization with market-driven efficiency. The study concludes that to ensure sustainable downstream development, Indonesia must reinforce institutional integrity, regulatory transparency, and environmental responsibility. The Indonesian experience thus offers valuable lessons for other resource-dependent nations pursuing structural economic transformation.